AN INFORMATION-PHYSICAL PERSPECTIVE ON FADING PROCESS TRANSITIONS BASED ON HIGHER ORDER STATISTICS - Panić, Stefan (Bulletin of Natural Sciences Research, 2025)
This paper proposes a novel theoretical framework for analyzing fading channels by introducing the concepts of energetic orbits and entropy barriers. Inspired by atomic physics and thermodynamic analogies, here the signal envelope is modeled as a stochastic process whose transitions between different structural regimes (extrema, inflection points, level crossings) correspond to energy quantization events. Each transition is associated with a local information-energy quantum, defined as a product of amplitude displacement and transition count, normalized by local entropy. Furthermore,   the ideas of entropic spin and degeneracy of states have been explored, and the dispersion of level-crossing processes, extremum-crossing process, inflection point-crossing process, saddle point-crossing process  (LCR, ECR, ICR, SCR) through an autocorrelation-based energetic formalism has been characterized. This approach enables the construction of a layered energetic map of fading dynamics and offers new insights into the structural behavior of wireless signals under stochastic fluctuations.
Keywords: Fading channels; Entropy barriers; Energetic orbits; Crossing statistics; Stochastic signal dynamics